If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 10 = 13x + -10 Reorder the terms: 10 + 11x = 13x + -10 Reorder the terms: 10 + 11x = -10 + 13x Solving 10 + 11x = -10 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 10 + 11x + -13x = -10 + 13x + -13x Combine like terms: 11x + -13x = -2x 10 + -2x = -10 + 13x + -13x Combine like terms: 13x + -13x = 0 10 + -2x = -10 + 0 10 + -2x = -10 Add '-10' to each side of the equation. 10 + -10 + -2x = -10 + -10 Combine like terms: 10 + -10 = 0 0 + -2x = -10 + -10 -2x = -10 + -10 Combine like terms: -10 + -10 = -20 -2x = -20 Divide each side by '-2'. x = 10 Simplifying x = 10
| 12z-7=-21+12z | | .05x=8.95 | | X^2+3i-2=0 | | 1.73=x*1.8+(1-x) | | 15=z+6+6 | | -(p-5)+7p=-5 | | 10m=10m+12 | | 4(2t-3)+3t=24+t | | -7m=-212 | | 2x+13=3x+9 | | (1x+8)(3x+4)=2 | | 12(2x-1)=3(8x+2) | | 9(2+1)=5(1-x) | | 11-y=14 | | 9147-391=9999-n | | 12(t-3)+6t=6(3t+2)-9 | | 8s+-32+-10s=-5 | | 45=12+7+5+12+Z+(Z+5) | | -4(1+x)=-3(5+2) | | 2-4x=-4-5x | | 8s+-32s+-10s=-5 | | .5x+x=60 | | x+yi=5 | | 2b+6b=7b-2 | | 7t+4=2(7+-5) | | 8-2x+5x=5 | | 4x^3+11x-3=0 | | 150-66=4q+3q^2 | | -14x+(-17x)= | | 1345+55=10+n | | .75x+7=19 | | N+(n+2)+(n+4)=243 |